PENGHIJAUAN BATARAN SINGAI WAMPU DI DESAN PANTAI GEMI KECAMATAN STABAT KABUPATEN LANGKAT - Fitria Fitria (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
The watershed is an ecosystem in which the elements of organisms nad biophysical environment and chemical elements interact dynamically and therein is a balance of inflow and outflow of material and energy. Flood problems are a problem that often occurs in this village from year to year.